Tuberculosis in workers of health facilities in the Callao Region: Tuberculosis among workers of health facilities in the Callao Region - Guerrero-Rodas, Ana María (2023)
Objective: To determine the characteristics of tuberculosis in the health personnel of the establishments of the Callao Region.Materials and methods. The study was cross-sectional descriptive. All health personnel who had tuberculosis while working in health facilities in the period 2013 to 2015 constituted the study population. Of 48 registered, 41 met the study criteria.Results. Of the total sample, 43.9% (n = 18) were nursing technicians, followed by nursing and administrative personnel. More than 90% of those affected had a hospital as a work center, 65.9% (n = 27) had pulmonary tuberculosis, 46.3% (n = 19) reported closed space, 34.1% (n = 14) with the presence of overcrowding. Regarding the use of N95 respirators, 46.3% (n = 19) did not use it, while 31.7% (n = 13) used it sporadically. Respect for the harmful habits of health workers, 61% (n = 25) showed consumption habits of alcohol and 36.6% (n = 15) for tobacco. Among the comorbidities present in health workers with tuberculosis, diabetes mellitus and depression stand out, in 34.1% (n = 14) and 17.1% (n = 7) respectively. Conclusions. Tuberculosis in health personnel affects mainly the technical nursing staff working in hospital establishments. A high percentage of health personnel with non-compliance with the protection measures was found. Keywords: Tuberculosis, Health Personnel, Healthcare Workers, Health Facilities, Peru (Source: MeSH, NLM)